Desempenho de reatores aeróbios de leito fluidizado com circulação interna na remoção de matéria carbonácea tratando diferentes águas residuárias - Correia, Gleyce Teixeira; Sanchez Ortiz, Ivan Andres; Gebara, Dib [UNESP]; Sobrinho, Milton Dall'Aglio [UNESP]; Matsumoto, Tsunao [UNESP] (Interciencia, 2012)
The organic matter. (OM) removal efficiency in the biochemical oxygen demand (BOD) and chemical oxygen demand (COD) forms for domestic wastewater and semi-intensive fish culture effluents by using three phase aerobic fluidized bed reactors with circulation in concentric tubes was studied. Three different ratios between external and internal areas by different internal diameter configurations (100, 125 and 150mm) to the same external diameter of 250mm were used; sand for filters and granulated activated carbon were used as supporting media. The reactors were tested for three hydraulic retention times: 11.5min to the R100, and 3h for the R125 and R150 reactors. The results demonstrated that this kind of reactors had good performance in the BOD and COD removal for different concentrations of waste waters. BOD mean removal efficiencies obtained were: 47% at the R100 reactor, 57% and 93% of raw and filtered BOD respectively at R125, 48 and 89% of raw and filtered BOD at R150. The COD mean calculated removal efficiencies were: 75% at the R100 reactor, 56 and 86% of raw and filtered COD at R125, and 54 and 86% of raw and filtered COD at R150. In the case of domestic wastewater it is necessary to provide a solids removal system at the reactor outflow in order to increase the removal of suspended OM from the final effluent.
Performance of fluidized bed aerobic reactors with internal circulation in the removal of organic matter from different residual waters